The Mediating Role of Growth Mindset in The Relationship Between Grit and Resilience Among Farmers in Coastal Area - Egi Prawita; Mega Handayani; Deni Santi Pertiwi (Universitas Katolik Soegijapranata, 2025)
Coastal farmers face various challenges, and they who possess perseverance and passion for long-term goals tend to develop a growth mindset that develop their resilience so they can overcome and recover from difficulties. This study aims to examine the relationship between grit and resilience mediated by growth mindset among coastal farmers in Kulon Progo Regency. The is a quantitative correlational study method involving 136 participants. The measurement tools used were the Indonesian versions of the CD-RISC-25, the Indonesian version of the Short Grit Scale (Grit-S), and the growth mindset scale. Mediation analysis using JASP showed that growth mindset partially mediated the relationship between grit and resilience. A significant positive indirect effect was found between grit and resilience through growth mindset (p = 0.002). However, the direct effect between grit and resilience was negative (p 0.001), and the total effect was not significant. These findings suggest that grit alone does not always lead to greater resilience, emphasizing the importance of growth mindset in shaping farmers’ psychological strength.